Clinical Surveillance and Evaluation of Suspected Ebola Cases in a Vaccine Trial During an Ebola Epidemic: The Sierra Leone Trial to Introduce a Vaccine Against Ebola - Conteh, Muhammad-Abbas (J Infect Dis, 2018)
The Sierra Leone Trial to Introduce a Vaccine Against Ebola (STRIVE), an Ebola vaccine trial conducted during the 2014–2016 Ebola epidemic, coordinated with the Sierra Leone national response to identify Ebola cases among trial participants. The early symptoms of Ebola are similar to common vaccine reactions, so it was important to differentiate these to avoid unnecessary referral to an Ebola facility and an increased risk of Ebola exposure. STRIVE developed a modified version of the national case definition and case management algorithm to distinguish between symptoms associated with both Ebola and vaccination with the candidate Ebola vaccine (rVSV∆G-ZEBOV-GP) from those typically associated only with Ebola. For participants who presented ≤48 hours after vaccination, we used the more stringent modified case definition to trigger referral for Ebola evaluation. Participants whose symptoms did not meet case definitions could also be referred to an Ebola facility, based on clinical judgment. No Ebola cases were diagnosed among the 8651 STRIVE participants. Fifty participants were evaluated for Ebola, of whom 34 (68%) were tested after vaccination; 22 deceased participants, all of whom underwent postmortem Ebola testing, as required during the Ebola epidemic, and had negative test results, were excluded from analysis. Seven of 34 participants (21%) had symptom onset ≤48 hours after vaccination, of whom 3 met the modified case definition. The most common diagnosis among those evaluated for Ebola was malaria. STRIVE demonstrates the feasibility of conducting Ebola surveillance among persons vaccinated with rVSV-ZEBOV during an Ebola epidemic and introduces a modified case definition and case management algorithm to distinguish vaccine reactions from early symptoms of Ebola that may be useful for reducing unnecessary Ebola evaluations among persons vaccinated during Ebola outbreaks. CLINICAL TRIALS REGISTRATION: ClinicalTrials.gov [NCT02378753] and Pan African Clinical Trials Registry [PACTR201502001037220].